The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3892/etm.2016.3701
|View full text |Cite
|
Sign up to set email alerts
|

Gender impact on the correlation between thyroid function and serum lipids in patients with differentiated thyroid cancer

Abstract: The present study aimed to explore the association between thyroid stimulating hormone (TSH) and serum lipids in patients with differentiated thyroid cancer (DTC), with a focus on the risk of hyperlipidemia between different genders. The study included 352 DTC patients who were ready to receive I-131 therapy as well as 352 matched normal controls. In the DTC group, 157 patients were monitored for TSH and lipid parameters prior to and after 1 month of thyroxine therapy. Results were analyzed using t-tests, Pear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Thus, the results of the present study indicate that sex hormones may actively contribute to atherosclerosis disease development. Li et al and Tognini et al also found that the gender difference had considerable effects on the association between TSH levels and serum lipid levels, and their conclusions were in agreement with those of the present study 38,39 .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the results of the present study indicate that sex hormones may actively contribute to atherosclerosis disease development. Li et al and Tognini et al also found that the gender difference had considerable effects on the association between TSH levels and serum lipid levels, and their conclusions were in agreement with those of the present study 38,39 .…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, this is the first study to show that normal TSH levels are associated with increased hypercholesterolemia risk in DTC patients receiving levothyroxine after total thyroidectomy. Although changes in the serum lipid levels during thyroxine withdrawal after total thyroidectomy have been assessed in some studies, the risk of hypercholesterolemia during levothyroxine therapy has not been [22,23,24,25]. Owing to the fact that thyroid cancers are detected early these days, leading to a low risk, and that most DTC patients have a favorable clinical course [26], the unsuppressed range of TSH may be applied to many such cases according to current management guidelines [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hard cardiovascular outcomes such as myocardial infarction, stroke, and death were not assessed, although hypercholesterolemia is a major risk factor for cardiovascular disease [28]. Third, our results may not be directly generalizable to male patients, because of the potential interaction of sex with the relationship between thyroid function and lipid metabolism [23,29]. Fourth, as this was a single-center study mainly comprising middle-aged patients in Korea, the findings should be interpreted with caution when applied to patients with different genetic, demographic, or geographic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…In an Israeli cohort study, TC survivors showed higher all-cause mortality with a higher prevalence of dyslipidemia and CVD than matched individuals without TC (17). Similarly, Li et al showed that after thyroidectomy, the risk of dyslipidemia markedly increased in patients with differentiated TC (22). When the changes in serum cholesterol levels were evaluated according to postoperative TSH levels, patients receiving levothyroxine after total thyroidectomy with normal TSH levels had a higher risk of hypercholesterolemia than did those with mildly suppressed TSH levels (18).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, opposite changes occur in conditions resulting from thyroid hormone deficiency (12)(13)(14). However, only few studies have investigated dyslipidemia risk in patients with TC, and these have yielded conflicting results (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), possibly because of differences in the study population, sample size, and follow-up period.…”
Section: Introductionmentioning
confidence: 99%